Neonatal Arterial Morphology Is Related to Body Size in Abnormal Human Fetal Growth. (September 2016) - Olander, Rasmus F.W.; Sundholm, Johnny K.M.; Ojala, Tiina H.; Andersson, Sture; Sarkola, Taisto
Abstract : Background—: Restriction in fetal growth is associated with cardiovascular disease in adulthood. It is unclear whether abnormal intrauterine growth influences arterial morphology during the fetal or neonatal stage. The objective was to study the regional arterial morphology with respect to gestational age and abnormal fetal body size. Methods and Results—: We studied body anthropometrics and arterial morphology and physiology in 174 neonates born between 31 and 42 weeks of gestation, including neonates with birth weights appropriate, small, and large for age, with very high resolution vascular ultrasound (35–55 MHz). In simple linear regressions, parameters of body size (body weight, body surface area, and organ circumference) and gestational age were statistically significantly associated with common carotid, brachial, femoral arterial parameters (lumen diameter [LD], wall layer thickness [intima-media thickness and intima-media-adventitia thickness], and carotid artery wall stress [CAWS]). Male sex was statistically significantly associated with LD and CAWS. In multiple linear regression models, body size, gestational age, and sex explained a large proportion of the arterial variance ( R 2 range, 0.37–0.47 for LD; 0.09–0.35 for intima-media thickness; 0.21–0.41 for intima-media-adventitia thickness; and 0.23 for CAWS; all models P <0.001). Arterial wall layer thickness, LDs, and CAWS were independently and strongly predicted by body size, and no effect of maternal disease was observed when added to the models. Gestational age and male sex were also independently but more weakly associated with arterial LDs and CAWS ( P <0.01), but not with arterial wall layers. Conclusions—: These results indicate that the intrauterine growth of fetal arterial LD and wall layer thickness are primarily attributed to body growth overall. LD and CAWS show weaker association with gestational age and sex. Abstract : Supplemental Digital Content is available in the text.